Strategi Perguruan Tinggi Islam Menuju World Class University - Zakki, Mohammad; Sokib; Syafi’i, Asrof (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
World class university is an important task for Islamic religious universities which are currently facing global challenges. Islamic religious tertiary institutions are increasingly experiencing significant development from a development perspective. In order to be able to compete with other tertiary institutions, the substance must also be developed in line with the need to become world class. This research is in the form of library research. The aim is to encourage Islamic religious tertiary institutions to be able to compete professionally with state universities. The data collection technique uses literature study, then content analysis is carried out and it is described broadly and in depth. The results of this study are: universities have a responsibility in supporting development in Indonesia, preparing humans as knowledgeable, civilized, skilled members of society supported by broad and deep scientific insights, and Islamic religious universities must make systemic and sustainable efforts to become education providers who are responsive to the changes and needs of society in the midst of globalization and the digital world.